Category of Discrete Dynamical System - Permatasari, Ananda Ayu; Carnia, Ema; Supriatna, Asep Kuswandi (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
A dynamical system is a method that can describe the process, behavior, and complexity of a system. In general, a dynamical system consists of a discrete dynamical system and a continuous dynamical system. This dynamical system is very interesting if seen from the algebraic side. One of them is about category theory. Category theory is a very universal theory in mathematical concepts. In this research, the dynamical system used is a discrete dynamical system represented as a directed graph with nodes in the graph called states. This discrete dynamical system has a height which is shown on the dynamical map in which the number of states at each height is called a profile. In this research, it will be proved whether the discrete dynamical system with the same profile is a category. Also, why category theory is needed in discrete dynamical systems will be investigated. The result of this study shows that the discrete dynamical system with the same profile is a category with its morphism is an evolution from one state to another state in different dynamical systems. Furthermore, category theory is needed for discrete dynamical systems to know about the properties and structure of discrete dynamical system.